Random walks : essays in elective criticism - Solway, David, 1941- (McGill-Queen's University Press, 1997)
The first section of the book develops Solway's approach to literature, starting from the assumption that genuine criticism requires the intellectual freedom to range at will across the literary landscape rather than restricting one's direction based on what is current, fashionable, or politically correct. Solway argues that advocating a theoretical school - postmodernism, poststructuralism, semiotics, new historicism, Marxist revisionism, or queer theory - generally involves abandoning the real critical project, which is the discovery of one's own undetermined motives, dispositions, and interests as reflected in the secret mirrors embedded in literary texts. Instead Solway pursues what he calls elective criticism, writing that enables the critical writer to freely discover his or her own identity - a concept that he claims cannot reasonably be diluted, relinquished, or deconstructed. In the second section Solway practices what he preaches, exploring a wide range of authors and subjects. His essays include an analysis of Franz Kafka's The Trial as a Jewish joke, a personal memoir of Irving Layton, an interpretation of Erin Moure's "Pronouns on the Main," an examination of language in William Shakespeare's romances, a reading of Robert Browning's "My Last Duchess" that is sympathetic to the Duke, an assertion that James Joyce has more in common with the traditional novelist than with the professional, (post-)modern alienator, and an exploration of Jonathan Swift's sartorial imagery that contends that form is the source of substantive identity.